Predictors of Tracheostomy Decannulation in Adult Laryngotracheal Stenosis. (June 2021) - Snow, Grace E.; Shaver, Timothy Brandon; Teplitzky, Taylor B.; Guardiani, Elizabeth
Objective: Predictors of tracheostomy decannulation in patients with laryngotracheal stenosis are not fully known, making prognosis difficult. The aim was to identify predictors of tracheostomy decannulation in adult patients with acquired stenosis of the larynx and/or trachea who were tracheostomy dependent. Study Design: Case series. Setting: Academic teaching hospital. Methods: A total of 103 consecutive adult patients with laryngotracheal stenosis who were tracheostomy dependent and seen by the otolaryngology clinic from January 1, 2013, to August 2, 2018, were included. Exclusion criteria included age <18 years, history of laryngeal cancer or head and neck radiation, or history of laryngeal fracture. The primary outcome was the presence of tracheostomy at last follow-up. The patients' etiology of stenosis, comorbid conditions, and characteristics of the stenosis were analyzed to determine if there was a statistically significant relationship with decannulation. Results: A total of 103 patients were included: 67% of patients were women and the average age was 53.5 years. Sixty-four patients (62%) were successfully decannulated. In multivariate analysis, patients who were successfully decannulated presented to the otolaryngology clinic earlier after tracheostomy was performed, were more likely to have been intubated due to trauma, and were less likely to have gastroesophageal reflux disease. In patients with subglottic or tracheal stenosis, those with granulation tissue without firm scar were more likely to be decannulated, and those who underwent rigid dilation were less likely to be decannulated. Conclusion: Early evaluation by an otolaryngologist may increase the likelihood of tracheostomy decannulation in patients with laryngotracheal stenosis. Patient comorbidities may assist in predicting which patients will be successfully decannulated.